The role of CAFs in therapeutic resistance in triple negative breast cancer: an emerging challenge - Brogna, Marianna Rita; Varone, Valeria; DelSesto, Michele; Ferrara, Gerardo (Frontiers in Molecular Biosciences, 2025)
The tumor microenvironment (TME) is a crucial element of cancerous tissue and has emerged as a promising target for therapeutic strategies. The complex variety of stromal cells within the TME plays a vital role in determining the tumor’s aggressiveness and its resistance to treatment. Tumor progression is not solely driven by cancer cells harboring genetic mutations but is also significantly influenced by non-cancerous host cells within the TME, which strongly impact tumor growth, metastasis, and the response to therapies. Cancer-associated fibroblasts (CAFs) are a diverse group of stromal cells within the TME. They play dual roles, both promoting and inhibiting tumor growth, making them intriguing targets for enhancing cancer therapies. Their significant contribution to creating a tumor-supportive environment has diminished the effectiveness of various cancer treatments, including radiation, chemotherapy, immunotherapy, and hormone therapy. Research has increasingly focused on understanding how CAFs contribute to therapy resistance in triple-negative breast cancer (TNBC) to improve treatment outcomes. However, the ways in which CAF patterns affect the TME and the response to immunotherapy in TNBC are not yet well understood and the interactions between CAFs, tumor cells, and immune cells in TNBC remain largely unexplored. In this review, we thoroughly exam ine the relationship between TNBC progression and CAF patterns. We discuss the current understanding of CAF heterogeneity, their role in tumor progression, and their impact on the tumor’s response to therapeutic agents in TNBC. Additionally, we explore the potential and possible strategies for therapies targeting CAFs.